Nosotras somos la amenaza - Darling, Victoria (2010)
The proposal of this paper is to build some “word pictures” of the contemporary resistance ways of Bolivian women, exemplified in stories of practices that occurred in conflicting events in the city of El Alto. The images are described in order to show the transformation of their actions, accompanied by stories that alsoshow the disruptive of their participation in the daily political work. This ethnographic exercise ends with a reflection of El Alto women who participated in the blockade of the city in October 2003.